Effectiveness of Project Based Learning Model with Canva Media Assisted in Islamic Education Learning - Risa Aprianty; Efi Tri Astuti (JIE (Journal of Islamic Education), 2024)
This study aims to measure the effectiveness of the Project Based Learning model assisted by Canva Media in Islamic Education learning. This study uses a Quantitative approach with the Experimental method of the actual experimental model. The study was conducted at SDN Sambong 2 Pacitan with 38 students as respondents, divided into 19 students in the control class and 19 in the experimental class. The data analysis technique used was the N-Gain Test. The study results showed that Islamic Education Learning through the PBL model assisted by Canva media consists of three main stages: planning, implementation, monitoring and evaluation. The concept of Islamic Education learning is quite effective in implementing it and is more effective than conventional learning. This is evidenced by the N-Gain test results for Project Based Learning assisted by Canva media which is more significant than traditional learning (67%> 61%). This study needs to consider other variables such as students' and teachers' technological abilities, which can affect learning outcomes. This study underlines innovation in technology and digital media as an integral part of religious learning, which has yet to be widely explored in previous studies.